The procedural side of the rule of law in the observations with anthropological bias - K. V. Aranovskiy; S. D. Knyazev (Правоприменение)
The subject. The article examines a wide range of issues related to the understanding of the role and importance of legal procedures in their relationship with the rule of law. The authors pay special attention to the current state and trends in the development of legislative, administrative and judicial procedures in the Russian Federation.The purpose of the article is to assess the impact of legal procedures on the rule of law.The description of methodology. The authors use methods of complex analysis, synthesis, as well as formal-legal, comparative-legal, research methods in combination with the methodology of anthropological science.The main results and scope of their application. Reconciling public-imperious decisions, the procedure sometimes governs the behavior of the state itself and keeps it in check, bringing statehood closer to rule of law. The rule of law needs urgently and comprehensively a system of different legal procedures: judicial, public, contractual, arbitration, electoral, referendum, parliamentary, federal, municipal and administrative (fiscal, budgetary, licensing, control, jurisdictional). It would simply not be able to meet its purpose without such procedures, and the idea of the rule of law would remain non-binding.  Not every form and fiction performs law-saving work and it’s also true for the conditional ability of the authorities to create law and judge law.Conclusions. Procedures, their combinations are different in origin and in action, but the "non-procedural" legal statehood can not exist. Therefore, procedural violations-encroachments on the judicial, parliamentary, electoral process and other types of processes – are especially dangerous. Legal statehood based on trust is harmed by frequent changes in procedures. The evolutionary capacity of legislative changes is the condition of their viability.